Intra-Extramedullary Drainage as an Effective Option for Treatment of Intramedullary Ependymal Cyst of Thoracic Spine: Technical Note - Landi, Alessandro; Pietrantonio, Andrea; Marotta, Nicola; Mancarella, Cristina; Delfini, Roberto (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Background Intramedullary neuroepithelial cysts are extremely rare and only 15 cases have been reported in the literature. Clinico-radiological features are not indicative of a specific diagnosis; for this reason, diagnosis is based mainly on the histological features. In the literature, total surgical removal is considered the treatment of choice. The risk of recurrence is higher after partial removal and in cases of occlusion of intra-extramedullary shunt. For this reason, a surgical strategy that ensures the shunt patency in case of incomplete removal of the cyst becomes a very safe option for treatment of this pathology.Materials and Methods We report the case of a 51-year-old woman who was found to have a dorsal (D9) intramedullary neuroepithelial cyst. She underwent surgical treatment with partial removal and placement of a Nelaton drainage device (8 French) inside the intra-extramedullary shunt.Results The patient experienced a complete regression of preoperative symptoms and magnetic resonance imaging (MRI) follow-up showed no radiological evidence of recurrence 24 months after surgical treatment.Conclusion Spinal ependymal cysts show a high frequency of recurrence, especially in cases of partial removal of the cyst wall. Unfortunately, the cyst walls are often closely adherent to the spinal cord, making total removal impossible. Intra-extramedullary shunting is a viable option, although there is a high frequency of recurrence in cases of obstruction of the shunt. Placing an 8 Ch Nelaton drain between the dorsal columns is a reliable technique, especially in cases of partial removal. In fact, it allows continuous drainage of cyst fluid and subsequent resolution of symptoms, and it decreases the incidence of recurrences due to obstruction of the shunt.
Keywords: intramedullary ependymal cyst; cyst-subarachnoid shunt; neurophysiological monitoring; Nelaton drain